Kata depan PENGEMBANGAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA OLEH GURU BAHASA INGGRIS SEBAGAI BAHASA ASING DI DAERAH PEDESAAN DI INDONESIA - Novita Silta Pasutri (Indra Institute Research & Publication, 2021)
This research aims to explore the rural teacher’s strategies to develop students’ Higher Order Thinking Skills based on the 2013 curriculum in the rural area of Indonesia. The participant of this research is one English teacher who teach in the Junior High School in Gaung district. By using qualitative approach, the researcher collect the data employs non-participant observation in the teaching and learning process, interviewed the English teacher, also documents by collecting the lesson plan made by one of the English teacher. The result of this research showed that the teacher develop the students’ Higher Order Thinking Skills by determining learning objectives with the eight characteristics of the lesson plan for 2013 curriculum, teach through questioning with LOTS questions, practice before assessment but it’s not effective, also provide assessment and feedback. The researcher also found that the teacher miss the step of review, refine and improve because she did not collect the students’ feedback. Based on the finding above, the researcher conclude that the teacher has been trying to do the steps to develop the students’ HOTS, but the development of HOTS in the rural area is not reach the expectation of the Higher Order Thinking based on 2013 curriculum.